Working Capital Management on Profitability with Company Size as Moderating Variable - Dinarossi Utami; Frecilia Nanda Melvani (Jurnal Aplikasi Manajemen dan Bisnis, 2022)
The primary consumer goods sector is an industry that is not affected by economic growth but instead supports the Indonesian economy. This study examines the effect of working capital management on profitability with firm size as a moderating variable in companies in the primary consumer goods sector listed on the Indonesia Stock Exchange. The research sample was fifty-seven companies with a research period from 2010 to 2020. The data analysis techniques used were panel data regression analysis and Moderated Regression Analysis (MRA). The study's dependent variable is the company's profitability; the independent variable is working capital management, including cash turnover, inventory turnover and cash cycle, and several control variables such as debt, capital, income, quick ratio and current ratio. The results showed that with firm size as a moderating variable, there was an overall increase in the correlation to the profitability variable. The interaction of working capital management variables with company size strengthens the effect of working capital management variables on company profitability in the primary consumer goods sector.